The global prevalence of tooth wear in general population: a systematic review and meta-analysis - Salari, Nader; Sadeghi, Amir Hossein; Abdolmaleki, Amir; Zarei, Hosna; Ghaderi, Amir Hossein; Shohaimi, Shamarina; Mohammadi, Masoud (Elsevier, 2026)
Objective Tooth wear (TW), as a common dental challenge, refers to the loss of dental tissue with four types of Attrition, Erosion, Abrasion, and Abfraction. Since there are no scientific reports regarding the global TW prevalence, this study was designed to investigate the prevalence of TW worldwide. Study design Systematic review and meta-analysis. Methods Systematic search was conducted (by November 2024) in valid databases of PubMed, WoS, ScienceDirect, Scopus, Embase, and Google Scholar search engine using the main keywords of “Prevalence”, “Tooth wear”, “Erosion”, “Attrition”, “Abfraction”, and “Abrasion”. The I2 index was used to examine heterogeneity, and the Random Effect Model was used for meta-analysis (CMA v.2). Results Following the review of 133 eligible studies with the sample size of 92,153 individuals with TW, the global prevalence of TW was found to be 40.8 % (95 %CI: 36.7–45, I2: 99.1). Conclusion According to the high global prevalence of TW, the implementation of a comprehensive strategy by the health care system seems necessary to control TW occurrence and prevent the associated complications.